Desain Dan Analisis Pengaruh Parameter PI Pada Respon Sistem Kontrol Arus Purwarupa Kendaraan Listrik - Syah Hendri kurniawan; Fatkhur Rohman (Universitas Merdeka Malang, 2020)
At this time, there are many electric vehicle manufacturers in Indonesia. The main obstacle in building electric vehicles is the electric motor control system, usually electric vehicles use the BLDC motor type. However, this type of motor has more complex control than conventional DC motors, it requires an encoder sensor to read the rotation of the motor with high accuracy, and a motor controller that can accurately control the amount of current in the motor. Based on the problem, the purpose of this study is to analyze the BLDC motor current control system using odrive motor driver and PI regulation, so that PI parameter values can be obtained to obtain a stable motor current control system, which can also produce system stability with small errors when the system is running. The results of the study show that variations in the value of the PI constant and the load affect the stability parameters of the system under steady-state error, rise time, and overshoot. At the same time, a change in the PI constant does not have a significant effect on the stability parameters of the system.